2001
DOI: 10.1002/1521-4095(200110)13:20<1574::aid-adma1574>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Oxide Photonic Crystals Grown by a New Hybrid Method

Abstract: A simple methodfor the fabrication of anodic aluminum oxide films (AOFs) with perfectly ordered structures (see Figure) is presented by these authors. A common optical grating is used to prepattern the aluminum substrate, which is subsequently anodized under mild conditions to yield an AOF with a photonic bandgap in the visible region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 5 publications
(12 reference statements)
0
92
1
1
Order By: Relevance
“…7(a)). The ordering was achieved by a combination of a preanodization nanoimprint on aluminum and matching the nanoimprint pitch with proper anodization voltage [20,89]. The well-known alumina barrier layer between the bottom of the pores and the underlying aluminum was thinned down to a few Nano Res (2009) 2: 829 843 nanometers [20,90,91].…”
Section: Cds/cdte Npl Solar Cellmentioning
confidence: 99%
“…7(a)). The ordering was achieved by a combination of a preanodization nanoimprint on aluminum and matching the nanoimprint pitch with proper anodization voltage [20,89]. The well-known alumina barrier layer between the bottom of the pores and the underlying aluminum was thinned down to a few Nano Res (2009) 2: 829 843 nanometers [20,90,91].…”
Section: Cds/cdte Npl Solar Cellmentioning
confidence: 99%
“…As it can be predicted, despite its costliness and additional complexities, lithography aided Al pre-texturing does away the need to perform double/multiple anodizations since high pore ordering is readily obtained through a single anodization process. The following are the major routes taken to achieve ideal pore arrangements in anodic alumina: -Imprint lithography (pattern transfer via embossing with a SiC mold [Masuda et al, 1997], SiN mold [Choi et al, 2003], commercial grating [Mikulskas et al, 2001], etc. ), -Focused ion-beam lithography (direct writing on Al [Peng et al, 2005;Robinson et al, 2007] or via photoresist patterning [Liu et al, 2003]), -Interference/holographic lithography (laser interference [Sun & Kim, 2002;Krishnan & Thompson, 2007]), -Pattern transfer via nano-sphere lithography (self assembly of colloidal particles followed by embossing [Fournier-Bidoz et al, 2004] or reactive-ion etching ), and -Pattern transfer via (Al) deposition on nano-structured substrates [Nishio et al, 2008].…”
Section: Highly Ordered Porous Aluminum Oxide Films By Aluminum Pre-tmentioning
confidence: 99%
“…Porous anodic alumina (PAA) has long been considered a promising material for templated growth of nanostructured materials for application in electronics, magnetics and optics [1][2][3], as well as mask for pattern transfer through wet and dry etching [4]. Since Masuda et al [5] reported the formation of highly ordered porous layers of aluminum oxide with a hexagonal configuration, an increasing emphasis has been put on PAA capabilities to give easy access to a self-organized ordered array of hexagonal pores with high aspect ratio and tunable pore size, with exceptional thermal stability over a wide range of temperature.…”
Section: Introductionmentioning
confidence: 99%